PERANAN PEMERINTAH DAERAH DALAM UPAYA PENANGGULANGAN EKSPLOITASI TERHADAP ANAK DI KOTA BENGKULU BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Riri Tri Mayasari; Mikho Ardinata (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: The problem of child exploitation is considered widespread in the community because there are many children employed as road workers. There are no age restrictions for families whose economy is insufficient to employ their children to support the economy. Bengkulu City is one of the areas where there are child problems that are quite worrying. The number of street children in Bengkulu City on highways such as Simpang Lima, Simpang Jam, and other locations shows that there are problems in the lives of children in Bengkulu City, efforts by the local government to overcome the crime of child exploitation in the city of Bengkulu. The government is responsible for providing free education and/or support or special services to children from disadvantaged families, neglected children, and children in remote areas.Keywords: local government; child exploitation